MOTIVASI KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA GURU SMK SWASTA DI WILAYAH TIMUR KABUPATEN PEMALANG - Hakim, Arif Rahman; Muhdi, Muhdi (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2019)
The purpose of this study is to (1) To find out the importance of work motivation on vocational teacher job satisfaction in the supervision of the eastern part of Pemalang Regency, (2) to find out the effect of compensation on job satisfaction of private Vocational Teachers in the supervisory area of the eastern part of Pemalang Regency, (3) to determine the effect of work motivation and compensation on job satisfaction of private vocational school teachers in the supervisory region of the eastern part of Pemalang Regency. Data collection method used was a questionnaire method. Analysis of the data used is descriptive analysis, test requirements and hypothesis testing which includes simple linear regression analysis and multiple regression analysis. Factors that affect teacher job satisfaction include work motivation and compensation 54.4%, the remaining 45.6% is influenced by variables outside the study. Work motivation and compensation of teachers in private vocational supervisory regions in the eastern part of Pemalang Regency are categorized while the job satisfaction of teachers in private vocational supervisory areas in the eastern part of Pemalang district is categorized high.